Effect of a night game on actigraphy-based sleep quality and perceived recovery in top-level volleyball athletes - Vitale, J. A.; Banfi, G.; Galbiati, A.; Ferini-Strambi, L.; La Torre, A. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To evaluate actigraphy-based sleep quality and perceived recovery before and after a night game in top-level volleyball athletes. Methods: Data on sleep parameters were collected by actigraphy for 3 consecutive nights with 24 elite athletes (12 male and 12 female; mean age [SD] = 26.0 [3.4] y, age range = 20-33 y) during the competitive season 2016-17. Data from 1 night before and 2 nights after an official night match were studied, and athletes' subjective perception of recovery was evaluated by the Total Quality Recovery scale. The following actigraphic parameters were studied: time in bed, sleep latency, sleep efficiency, wake after sleep onset, total sleep time, immobility time, moving time, and fragmentation index. Results: The analysis highlighted significant differences for all sleep variables. Total sleep time was lower the first night after the match compared with prematch sleep (P = .02) and the second night (P = .0009) after night competition (P = .0001, F2,23 = 22.93, Eta 2 p = .66). Similarly, sleep efficiency was lower immediately after the night competition compared with both prematch values (P = .03) and the second night (P = .0003) after competition (P = .0005, F2,23 = 8.93, Eta 2 p = .44). The same differences were observed in the perceived recovery values (P = .001, F2,23 = 13.37, Eta 2 p = .54). Conclusions: Coaches and medical staff should use these findings to develop a greater knowledge of how sleep differs during different phases of competition and to implement behavioral and sleep-hygiene strategies in top-level athletes.